L1 Retrotransposons: A Potential Endogenous Regulator for Schizophrenia - Jahangir, Muhammad; Li, Li; Zhou, Jian-Song; Lang, Bing; Wang, Xiao-Ping (Frontiers in Genetics, 2022)
The long interspersed nuclear elements 1 (LINE-1/L1s) are the only active autonomous retrotransposons found in humans which can integrate anywhere in the human genome. They can expand the genome and thus bring good or bad effects to the host cells which really depends on their integration site and associated polymorphism. LINE-1 retrotransposition has been found participating in various neurological disorders such as autism spectrum disorder, Alzheimer’s disease, major depression disorder, post-traumatic stress disorder and schizophrenia. Despite the recent progress, the roles and pathological mechanism of LINE-1 retrotransposition in schizophrenia and its heritable risks, particularly, contribution to “missing heritability” are yet to be determined. Therefore, This review focuses on the potentially etiological roles of L1s in the development of schizophrenia, and possible therapeutic choices and raised unaddressed questions, in order to shed lights on the speculations to guide future studies. research.